Cellular response to rare earth mixtures (La and Gd) as components of degradable Mg alloys for medical applications - Grillo, Claudia Alejandra (2014)
Rare earth (RE) elements have been proposed to improve the corrosion resistance of degradable Mg alloys for medical applications. However, good biocompatibility of the elements released by Mg alloys during degradation is essential for their use in implants. Most studies are focused on material science and engineering aspects, but the effects of ions released at the biological interface are not frequently addressed. The aim of this study was to contribute to the knowledge of in vitro toxicological effects of two RE Mg-alloying elements, La and Gd, as individual ions and in mixtures with and without Mg ions. Different combinations (Mg + Gd, Mg + La, and Mg + Gd + La) were used to evaluate their possible synergistic effects on CHO-K1 cells. Two sets of experiments were designed to assess (1) the cyto-genotoxic effect of La and Gd ions by neutral red (NR) technique, Reduction of tetrazolium salt (MTT), Viability with Acridine Orange staining, Clonogenic test, and Comet assay; and, (2) the possible synergistic toxicological effect of La and Gd ions in mixtures, and the influence of osmolarity increase on cellular response. Cytotoxic effects of RE were found at concentrations ≥200 μM RE while DNA damage was detected for doses ≥1500 μM and ≥1600 μM for La and Gd, respectively. When mixtures of ions were evaluated, neither synergistic cytotoxic effects nor biological damage related to osmolarity increase were detected.